2019
DOI: 10.1002/ptr.6268
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic anti‐inflammatory effects of quercetin and catechin via inhibiting activation of TLR4–MyD88‐mediated NF‐κB and MAPK signaling pathways

Abstract: The synergistic anti‐inflammatory effect of quercetin and catechin was investigated using lipopolysaccharide (LPS)‐stimulated macrophage RAW 264.7 cells. Results showed that the combined treatment of quercetin with catechin synergistically attenuated LPS‐stimulated increase of some proinflammatory molecules, including nitric oxide, tumor necrosis factor α, interleukin‐1β, nitric oxide synthase, and cyclooxygenase‐2. Moreover, it exhibited significantly (p < 0.05) stronger inhibitory effect on nuclear transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 37 publications
6
44
0
1
Order By: Relevance
“…For instance, catechin derivatives such as epigallocatechin gallate and epicatechin gallate were previously isolated from A. crassna leaves [44]. Recent studies have revealed that catechins exhibit anti-inflammatory activity via wide range of mechanisms [45,46]. Figure S14).…”
Section: Benzophenonesmentioning
confidence: 99%
“…For instance, catechin derivatives such as epigallocatechin gallate and epicatechin gallate were previously isolated from A. crassna leaves [44]. Recent studies have revealed that catechins exhibit anti-inflammatory activity via wide range of mechanisms [45,46]. Figure S14).…”
Section: Benzophenonesmentioning
confidence: 99%
“…In addition, it has been revealed that cyanidin-3-glucoside ameliorates the LPS-induced secretion of proinflammatory cytokines including TNF-α and IL-6 in human umbilical vein endothelial cells (HUVECs) [30]. Moreover, flavonols found in HM such as rutin [31], astragalin [32], quercetin [33,34], and kaempferol [35,36] have been reported to have anti-inflammatory effects. Rutin inhibited palmitic acid-induced inflammation in macrophages by suppressing the genes related to endoplasmic reticulum (ER) stress [31], while astragalin inhibited LPS-induced NO production and expression of proinflammatory mediators such as NOS2 and PTGS2 in J774A.1 mouse macrophages [32].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the synergistic effect of quercetin and catechin (or docosahexaenoic acid) has been reported by reducing pro-inflammatory cytokines and NF-kB activation via inhibiting MAPK signaling in LPS-treated Raw264.7 cells [45,46]. The combination of quercetin and galangin has also shown improved anti-inflammatory effects in the mouse model of atopic dermatitis [47].…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic acid and flavonoid analysis used the mobile phase containing 2% glacial acetic acid in water (Solution A) and 2% glacial acetic acid in acetonitrile (Solution B). The ratio of solution based on B was 15%, 5%, 15%, 5%, 10%, 50%, 50%, 60%, 80%, and 90% at 10,15,20,25,30,35,40,45,55, and 60 min, respectively. The injection volume was 20 µL, and the flow rate was 1.0 mL/min at 30 • C. The detection wavelength was 280 and 270 nm for phenolic acids and flavonoids, respectively.…”
Section: High-performance Liquid Chromatography (Hplc)mentioning
confidence: 98%